2016
DOI: 10.1161/circulationaha.116.023309
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Duration of Resuscitation and Favorable Outcome After Out-of-Hospital Cardiac Arrest

Abstract: Background Little evidence guides the appropriate duration of resuscitation in out-of-hospital cardiac arrest (OHCA), and case features justifying longer or shorter durations are ill-defined. We estimated the impact of resuscitation duration on the probability of favorable functional outcome in OHCA using a large, multi-center cohort. Methods Secondary analysis of a North American, single blind, multi-center, cluster-randomized clinical trial (ROC-PRIMED) of consecutive adults with non-traumatic, EMS-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 37 publications
(40 reference statements)
3
114
3
4
Order By: Relevance
“…These data do not address the possibility of combining sodium bicarbonate along with extracorporeal membrane support or administration earlier in the resuscitation. We have previously reported most favorable outcomes are achieved with shorter resuscitation intervals (22,23).…”
Section: Discussionmentioning
confidence: 91%
“…These data do not address the possibility of combining sodium bicarbonate along with extracorporeal membrane support or administration earlier in the resuscitation. We have previously reported most favorable outcomes are achieved with shorter resuscitation intervals (22,23).…”
Section: Discussionmentioning
confidence: 91%
“…6-8, 11 In these studies, patients with non-shockable rhythms were older than those with shockable rhythms. In the present study, the proportion of nonshockable rhythm increased with age.…”
Section: -11mentioning
confidence: 85%
“…1- 4 Recently, several studies have investigated the relationship between CPR duration and outcome, and in particular according to initial documented rhythm. [5][6][7][8][9][10][11] crew consists of 3 EMS staff members, including at least 1 emergency lifesaving technician (ELST). ELSTs are allowed to use various resuscitation methods, including for whom resuscitation was attempted after OHCA in Japan between January 2011 and December 2014.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…In a recent analysis, the elapsed duration at which the probability of survival fell below 1% was 48 and 15 min in the shockable and non-shockable groups, respectively (52). A secondary analysis of 11,368 cases of OHCA from the US ROC-PRIMED (Resuscitation Outcomes Consortium Prehospital Resuscitation Using an Impedance Valve and Early Versus Delayed) identified that that with conventional resuscitation, 90% of patients with good outcome achieved initial ROSC within 20 minutes and 99% within 37 minutes (53). There were no survivors with favourable neurological outcome where ROSC occurred after 47 minutes.…”
Section: Refractory Arrest: Transport or Termination Of Resuscitation?mentioning
confidence: 99%